5G radio access above 6 GHz. Issue 9 (4th August 2016) - Shariat, Mehrdad; Gutierrez‐Estevez, David M.; Vijay, Arnesh; Safjan, Krystian; Rugeland, Patrik; da Silva, Icaro; Lorca, Javier; Widmer, Joerg; Fresia, Maria; Li, Yilin; Siaud, Isabelle
Abstract: Designing and developing a millimetre‐wave (mmWave)‐based mobile radio access technology (RAT) in the 6–100 GHz frequency range is a fundamental component in the standardisation of the new 5G radio interface, recently kicked off by 3rd Generation Partnership Project. Such component herein called the new mmWave RAT will not only enable extreme mobile broadband services but also support ultra‐high definition/three‐dimensional streaming, offer immersive applications and ultra‐responsive cloud services to provide an outstanding quality of experience to the mobile users. The main objective of this paper is to develop the network architectural elements and functions that will enable tight integration of mmWave technology into the overall 5G radio access network. A broad range of topics addressing mobile architecture and network functionalities will be covered–starting with the architectural facets of network slicing, multi‐connectivity and cells clustering, to more functional elements of initial access, mobility, radio resource management and self‐backhauling. The intention of the concepts presented here is to lay foundation for future studies towards the first commercial implementation of the mmWave RAT above 6 GHz. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The main objective of this paper is to develop the network architectural elements and functions that will enable tight integration of mmWave technology into the overall 5G radio access network (RAN). A broad range of topics addressing mobile architecture and network functionalities will be covered–starting with the architectural facets of network slicing, multi‐connectivity and cells clustering, to more functional elements of initial access, mobility, radio resource management (RRM) and self‐backhauling.